Inter-war period safe-breakers. An environmental analysis based on Warsaw (Archives of Criminology, 2023)
The interwar period is sometimes described as the golden era of safe-breakers. This era is said to have begun at the beginning of the twentieth century, whereas the second half of the 1930s marks its end. The largest group of safe-breakers was comprised of criminals from Warsaw (over 200 people). This article attempts to analyse this environment with additional elements of prosopography. I would like to answer the question of who these safe-breakers of Warsaw during the interwar period were and to attempt to reconstruct the courses of their ‘careers’ alongside the question of motive. An especially interesting aspect is their social background. The article concludes with thoughts on the connections between the reality at that time and the current idea of an interwar safe-breaker.